Assesment of Pumping Requirements in DEMO Reactor. (17th November 2017) - Igitkhanov, Yu.; Day, Ch.; Lang, P.; Plöckl, B.
Abstract: We analyze requirements on the particle throughput inside the torus, posed by the different physics processes during the DEMO inductive operation needed for tritium plant fuel processing, pumping and fueling systems design. Unlike ITER in DEMO limitations posed by pumping and tritium plant systems are expected to be more moderate because of employing advanced solutions. However, the requirements on the particle throughput posed by plasma processes in DEMO are found to be more demanding and the way of their reduction by bypassing, recycling etc. to be mandatory.